PENJUALAN LOKAL DAN EKSPOR PRODUK TEH PT. PAGILARAN - , NITA NURINTAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Agricultural land and farm managementare surely carried outwell. Establishing a businessin the field of agro-processing and farmis the idea of some people who live in an agricultural area. Good marketing increases the sales. One of the companies working in the field of crop processing is PT. Pagilaran. This company has tea as its excellent products which are sold locally and also export. Methods of data analysis used to determinethe percentage of sales of each type of tea which is sold locally and export at PT.Pagilaran are descriptive statistical methods which are related to the collection and presentation of a range of data so that it can provide useful information. The calculation shows the percentage of sales comparisons as follows: local sales in 2011 has a larger number of 56.73% compared to the number of exportin the same year which is 43.27%, local sales in 2012 is 60.09% and it is larger than export in 2012 which is only 39.91%, while local sales in 2013 is 69.70% and it is larger than export in 2013 which is 30.30%. PT. Pagilaran does notuseany distribution agencies for their sales so that tea will be sent directly from the factory to the consumers and pass through the administrative process administered by the board of directors. The problem which is often experienced by PT. Pagilaran is the in adequate transportation.